The effects of shared vision on value co-creation in megaprojects: A multigroup analysis between clients and main contractors. Issue 3 (April 2022) - Chi, Ming; Chong, Heap-Yih; Xu, Yongshun
Highlights: Shared vision acts as an antecedent variable for value co-creation in megaprojects. Requirements risk and dysfunctional competition were tested as contextual variables. A multigroup analysis reveals new and distinguished effects to the key stakeholders. Actionable strategies are proposed for megaproject management. Abstract: Value co-creation is a new and important organisational strategy for addressing complex and fragmented practices in megaprojects. However, the existing literature rarely explores the influences of shared vision on value co-creation in megaprojects. Hence, this study aims to explore the relationship between shared vision and value co-creation, and the main factors that moderate it from the perspectives of clients and main contractors. The results reveal that shared vision can improve value co-creation and that its influence is moderated by requirements risk and dysfunctional competition, which serve as environmental and institutional factors. Specifically, for main contractors, requirements risk strengthens the positive effect of shared vision and value co-creation, whereas dysfunctional competition mitigates it. For clients, dysfunctional competition attenuates this relationship, while requirements risk exerts no significant moderating effect. This research contributes to the knowledge advancement and managerial implications of value co-creation for both clients and main contractors in megaprojects.